Internet of Things for architects : architecting IoT solutions by implementing sensors, communication infrastructure, edge computing, analytics, and security /: architecting IoT solutions by implementing sensors, communication infrastructure, edge computing, analytics, and security. (2018) - Lea, Perry
No abstract available